REMOTE MONITORING SYSTEM USING IoT - Pitchaimuthu, Arunagiri (IJRDO - Journal of Electrical And Electronics Engineering, 2018)
To create an intelligent sensor framework for monitoring the industrial environment using the beagle board. The framework of the monitoring system is established on the arrangement of distributing unis. It can be implemented by connecting many sensors to display the various device activities and control those data from anywhere to provide greater flexibility to the user. The system which records the several kinds of parameters such as temperature, humidity and GPS. The sensor node consists of various sensor to display the temperature value, relative moisture and track the board where it is placed. MQTT (Message Queuing Telemetry Transfer) system is the backbone for the internet of things operation which provides the information and instructions. The beagle board will be receiving the data from the sensor and the board will be transfer the information to the MQTT broker protocol using dongle or Wi-Fi modem.